EFFECTIVE COMMUNICATION IN THE “THERAPIST – PATIENT” SYSTEM IN A CLINICAL INSTITUTION - Malyarova, Yu. M.; Soltyk, I. T.; Serbova, O. V. (Rehabilitation and Recreation, 2025)
Introduction. Effective communication between a therapist and a patient is a key factor in providing high-quality medical care. It influences the level of patient trust, adherence to treatment, therapy effectiveness, and overall satisfaction with medical services. However, communication barriers often arise in the interaction between a doctor and a patient, which can reduce the quality of treatment. Objective of the study. The aim of this study is to analyze the fundamental principles of effective communication between a therapist and a patient, identify barriers, and develop strategies to overcome them. Materials and methods. The study utilized the following methods: analysis of scientific literature on medical communication; a survey of 150 patients to assess their level of satisfaction with communication with a therapist; a survey of 30 therapists (including 20 physical therapists and 10 occupational therapists) to identify challenges in patient interaction; observation of 10 consultations to evaluate therapists’ verbal and non-verbal communication; and an experimental communication training program for therapists, with subsequent assessment of its impact on the quality of therapist-patient interaction. Results. The study identified four main groups of communication barriers: verbal barriers – the use of complex medical terminology and the lack of verification of patient understanding; non-verbal barriers – insufficient eye contact, closed posture, and a low level of active listening; psychological barriers – patient fear of diagnosis, low level of trust, and emotional burnout of patients due to the ongoing war in the country; organizational barriers – lack of time for consultations, absence of communication training for therapists, and insufficient use of digital technologies in rehabilitation. Conclusions. After conducting a short communication training program, several positive outcomes were achieved: after therapists completed the medical communication training, patient satisfaction with diagnosis explanations increased from 58 to 82%; the use of the «teach-back» technique increased by 30%, improving patient understanding of treatment recommendations; enhanced therapist empathy raised patient satisfaction with therapist interaction from 65 to 89%. The findings confirm the necessity of implementing communication skills training for therapists and other healthcare professionals.